[tex]\it A\cdot A = \begin{pmatrix}1\ \ \ 1
\\ \\
1\ \ \ 0\end{pmatrix} \cdot \begin{pmatrix}1\ \ \ 1
\\ \\
1\ \ \ 0\end{pmatrix} = \begin{pmatrix}2\ \ \ 1
\\ \\
1\ \ \ 1\end{pmatrix}[/tex]
[tex]\it xI_2 = x \begin{pmatrix}1\ \ \ 0 \\ \\ 0\ \ \ 1\end{pmatrix} = \begin{pmatrix}x\ \ \ 0 \\ \\ 0\ \ \ x\end{pmatrix}[/tex]
Relația din enunț devine:
[tex]\it \begin{pmatrix}2\ \ \ 1 \\ \\ 1\ \ \ 1\end{pmatrix} + \begin{pmatrix}x\ \ \ 0 \\ \\ 0\ \ \ x\end{pmatrix} =\begin{pmatrix}1\ \ \ 1 \\ \\ 1\ \ \ 0\end{pmatrix} \Rightarrow \begin{pmatrix}2+x\ \ \ \ \ 1 \\ \\ 1\ \ \ \ \ 1+x\end{pmatrix} =\begin{pmatrix}1\ \ \ 1 \\ \\ 1\ \ \ 0\end{pmatrix} [/tex]
Din identificarea termenilor, obținem:
2+x =1 ⇒ x =-1
1+x = 0 ⇒ x = -1